Artemisinin and Total Flavonoid Content in In Vitro Cultivted Artemisia annua L. "Hairy" Root Culture - Drobot, Kateryna; Matvieieva, Nadiia; Kharkhota Мaxim; Shakhovsky, Anatolii; Ratushnyak, Yakiv (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
In this paper artemisinin and total flavonoid content in in vitro cultivated non-transformed Artemisia annua L. plants and “hairy” root culture were compared. The amount of total flavonoids was determined using modified Aluminium chloride colorimetric method. Determination of artemisinin in Artemisia annua extracts was carried out using HPLC analysis. Transgenic roots of Artemisia annua accumulated flavonoids in more degree than the roots (1.8 times higher) and leaves (1.6 times higher) of in vitro cultivated control plants. At the same time the control roots synthesized artemisinin four times more (up to 6.5 mg/g dry weight) than “hairy” roots. Owing to the higher growth rate (almost 40 times higher in 3 weeks of cultivation) transgenic roots may be suitable for artemisinin production. The data obtained suggest the possibility of using of Artemisia annua “hairy” root culture as a potential source of flavonoids and artemisinin.